COVID‐19 in a high‐risk dual heart and kidney transplant recipient. Issue 7 (22nd June 2020) - Hsu, Jeffrey J.; Gaynor, Pryce; Kamath, Megan; Fan, Ashley; Al‐Saffar, Farah; Cruz, Daniel; Nsair, Ali
Abstract : The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is rapidly infecting people worldwide, resulting in the infectious disease coronavirus disease 19 (COVID‐19) that has been declared a pandemic. Much remains unknown about COVID‐19, including its effects on solid organ transplant (SOT) recipients. Given their immunosuppressed state, SOT recipients are presumed to be at high risk of complications with viral infections such as SARS‐CoV‐2. Limited case reports in single SOT recipients, however, have not suggested a particularly severe course in this population. In this report, we present a dual‐organ (heart/kidney) transplant recipient who was found to have COVID‐19 and, despite the presence of a number of risk factors for poor outcomes, had a relatively mild clinical course. Abstract : In this case report, a dual‐organ (heart/kidney) transplant recipient is diagnosed with COVID‐19 and, despite the presence of a number of risk factors for poor outcomes, has a relatively mild clinical course.